Child Rights Reflected In Jodi Picoult's My Sister's Keeper:A Sociological Perspective - Susila, Linda Ratna; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This study is about Child Rights in My Sister's Keeper novel. The problem of this study is a child that wants to get her right in medical emancipation. The object of the study is My Sister's Keeper novel by Jodi Picoult. It uses sociological perspective. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel and the secondary data is other materials related to the study. The result of the study shows the following conclusion, based on the analysis it shows that there is a close relation between the novel and the social reality in the late twentieth century and the early twenty first century. Jodi Picoult wants to show a child that wants to prosecute her mother in the court because she wants to get her right in medical emancipation.